Pengaruh Komposisi Komposit Gypsum Berpenguat Limbah Masker Medis Terhadap Transmission Loss - Nugroho, Daffa Aryo; Suardana, Ngakan Putu Gede; Kencanawati, Cok Istri Putri Kusuma (Teknik Desain Mekanika; Vol 10 No 3 (2022): Juli 2022 : Teknik Desain Mekanika, 2022)
Abstract Covid-19 virus pandemic that broke out in early March 2020 has played a major role in increasing the number of masks and personal protective equipment (PPE) waste due to preventing the further spread of the COVID-19 virus. According to the Indonesian Institute of Sciences (LIPI), there was 1,665.75 tons of medical mask and personal protective equipment waste from early March 2020 to September 2020. Due to the large amount of medical mask waste, it is necessary to immediately address it, such as recycling it into useful materials. This research was conducted to find a new alternative for treating medical mask waste by mixing gypsum with medical mask waste that has been sterilized and chopped. Gypsum used as a matrix and medical mask waste that has been sterilized and chopped will be reinforcement and applied as a sound-absorbing composite. This composite will be made using volume fractions of reinforcement 0%, 5%, 10%, and 15%. The transmission loss tests were carried out according to the ASTM E 90-09 standard. Specimens with a volume fraction of 5% reinforcement have the highest transmission loss value of 33.7 dB at a frequency of 500 Hz, while the smallest transmission loss value occurs in a specimen with a volume fraction of 15% reinforcement, which is 8 dB at a frequency of 1500 Hz. The composite structure of the matrix and reinforcement mixture can be seen from the results of the micro-photograph test. Keywords: Composite, sound absorption, gypsum, medical mask waste, transmission loss test